Penyelesaian Sengketa Wanprestasi Sewa-Menyewa Satelit Kemenhan RI Dengan Avanti Communications Secara Arbitrase - Ichsan Fadillah, Farhan; Riza, Faisal (Universitas Ekasakti, 2024)
This research discusses the resolution of the breach of lease dispute regarding satellite rental between the Ministry of Defense of the Republic of Indonesia and Avanti Communications through international arbitration, with a focus on analyzing the procedures conducted based on relevant regulations. The chosen research method is a normative approach utilizing primary legal sources from literature studies. The research aims to discuss dispute resolution strategies through international arbitration mechanisms in accordance with applicable laws. Arbitration is an option stipulated in a written agreement between parties aimed at resolving disputes outside conventional court processes. In the context of the case between Avanti Communications Limited and the Ministry of Defense of the Republic of Indonesia, it was proven that the Ministry of Defense committed a breach of contract and is required to compensate the losses incurred by Avanti Communications Ltd. The law on damages specifies the details that can be included. There is a potential for the cancellation of a legal agreement due to negligence that leads to a breach of contract, where the cancellation of the agreement can occur if it causes harm to the relevant parties.